PROFESIONALISME AUDITOR DALAM PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Andhika Kuntjoro (2020)
This research aims to examine and analyze the influence of time pressure, audit risk, materiality, and supervise against premature sign off in audit procedures. The sample of this research were 59 auditor in BPKP Pusat. The sampling method is purposive sampling. The analysis method uses Structural Equation Modelling (SEM) with Partial Least Squares (PLS) Path Modelling with SmartPLS 3.0 analysis tools. The result show that the materiality positive significantly influenced premature sign off in time pressure, audit procedures and audit risk and supervise have no significant effect or influence on the behavior of premature sign off in audit procedures.